2022
DOI: 10.1097/iop.0000000000002305
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Spindle Cell and Pleomorphic Lipomatous Tumor of the Ocular Adnexa: Two Cases of a Rare Entity

Abstract: : Atypical spindle cell and pleomorphic lipomatous tumor (ASCPLT) is a rare lipomatous neoplasm that was recently introduced into the World Health Organization Classification of Soft Tissue and Bone tumors as a distinct entity. ASCPLT has potential for local recurrence but does not metastasize. This biologic behavior separates ASCPLT from its morphologic mimics. Ocular adnexal ASCPLT has not been previously reported. Described herein are two patients with ASCPLT. The subcutaneous orbital rim lesion featured ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A large series of 232 atypical spindle cell lipomatous tumors reported that approximately two-thirds (63%) of the tumors occur predominantly in the limbs and limb girdles, although less commonly in the head and neck, genital area, trunk, and back [ 2 ]. To the best of our knowledge, ASC/ PLT in the ocular adnexa has been previously reported in only two cases: the orbital septum and eyelid [ 3 ]. According to Ulloa-Padilla et al [ 3 ], our tumor is differentiated from the other atypical lipomatous tumor/well-differentiated liposarcoma since MDM2 and CDK4 showed negative in immunohistochemical findings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A large series of 232 atypical spindle cell lipomatous tumors reported that approximately two-thirds (63%) of the tumors occur predominantly in the limbs and limb girdles, although less commonly in the head and neck, genital area, trunk, and back [ 2 ]. To the best of our knowledge, ASC/ PLT in the ocular adnexa has been previously reported in only two cases: the orbital septum and eyelid [ 3 ]. According to Ulloa-Padilla et al [ 3 ], our tumor is differentiated from the other atypical lipomatous tumor/well-differentiated liposarcoma since MDM2 and CDK4 showed negative in immunohistochemical findings.…”
mentioning
confidence: 99%
“…To the best of our knowledge, ASC/ PLT in the ocular adnexa has been previously reported in only two cases: the orbital septum and eyelid [ 3 ]. According to Ulloa-Padilla et al [ 3 ], our tumor is differentiated from the other atypical lipomatous tumor/well-differentiated liposarcoma since MDM2 and CDK4 showed negative in immunohistochemical findings.…”
mentioning
confidence: 99%